Impacto de una intervención sobre algunos parámetros de inflamación en pacientes con sobrepeso u obesidad con y sin síndrome metabólico - Rodríguez López, Carmen Paulina (Universidad Autónoma Metropolitana, 2019)
In the last decade it has been demonstrated that obesity entails adipose tissue immunophenotypic and systemic alterations, which are caused by the excessive and improper activation of the immune system. On that basis, a lowintensity chronic inflammatory process has been identified in the case of obesity as playing an important role in pathogenesis and the exacerbation of the metabolic anomalies of obesity, most notably in the cases of insuline resistence and generalised dyslipidemias like metabolic syndrome (MS). Therefore, it has been proposed that in order to tackle obesity and its associated immunometabolic alterations, interventions based on lifestyle modifications should be implemented, mainly those regarding increased physical activity and caloric restriction. The objective of this thesis was to analyse the changes in some systemic cells of the immune system together with changes in anthropometric, biometric and body composition measurements after the implementation of either a physical activity routine or a weight loss diet plan in young adults with overweight (OW) and obesity (Ob) either presenting MS or not. A medical history and weight, height and waist circumference (WC) measurements were obtained from each patient. A first classification of the patients’ state of nutrition was developed using weight and height measurements (normal weight, overweight or obesity). In addition, body composition was analysed using the Inbody720 and the Hologic Wi equipments. The Inbody720 was used to measure body weight and visceral adipose tissue (VAT), which allowed diagnose visceral obesity: presenting >100 cm2 of VAT would mean a visceral obesity diagnosis whereas <99 cm2 would be a normal VAT diagnosis. The Hologic Wi equipment was used to measure the SMM in kilograms and the percentage and kilograms of subcutaneous adipose tissue (ST and AM respectively). Biochemical tests were developed using the automatized iKEM equipment, obtaining triglyceride (TG), high-density cholesterol (HDL-c), glucose (Glu) and total cholesterol levels. The Friedewalt formula was used in order to obtain low-density cholesterol (LDL-c) levels (Total. Col. – (HDL-c+TG/5). Blood pressure was obtained complying with the Mexican Official Norm (NOM-030-SSA2-1999) standards for the prevention, treatment and control of hypertension and using an sphygmomanometer through duplication. The diagnosis of MS was obtained according to the National Cholesterol Education Program (ATP III: National Cholesterol Education Program Adult Treatment Panel III) adujsted to hispanic people. Finally, the percentages of some limphocytic subpopulations (total lymphocytes, monocytes, granulocytes, TCD3+, TCD4+, TCD8+, NK, and B lymphocytes, helper cells (CD4+CD62-), cytotoxic (CD8+CD28-), memory cells (CD45RO+) and naïve cells (CD45RA+) for TCD3+ and TCD4+) were obtained. While obtaining the above-mentioned data, a two-month intervention was undertaken, conducting either a physical activity routine or a weight-loss diet plan. By the end of the intervention period, all the afore-mentioned measurements were obtained again. The training stage was conducted through an adaption of the HighIntensity Interval Training (HIIT) while the diet plan was based on the Dietary Approaches to Stop Hypertension (DASH) diet. From September 2015 to January 2017, a total of 169 people averagely aged 26.4 ±6.8 years, participated in the research. 120 participants were women (71%) and 49 were men (29%). 34 participants (20%) presented a normal Body Mass Index (BMI) while 82 participants presented overweight. It was observed that as the BMI increased along with increased VAT, all the anthropometric, body composition and biochemical variables suffered significant negative alterations. In turn, the prevalence of MS was of 28% (n=45) and people with MS had the most highly significant numbers in WC, VAT, SMM and AM in relation to those subjects without MS. In addition, there was a positive correlation between VAT and SMM in people with and without MS, which was the strongest correlation among people with MS. Regarding leukocytic subpopulations, this research found that total lymphocytes increased significantly as BMI and VAT increased and MS was present. In turn, natural killer (NK) granulocytes and lymphocytes decreased significantly as BMI decreased, VAT increased and MS was present. In the analysis of effector cells no statistical differences were found when analysed in relation to BMI, MS or VAT. Also, it was observed that total memory cells (TCD3+CD45RO+) and TCD4+ cells increased significantly according to BMI and the increase in VAT. By way of contrast, TCD3+ (TCD3+CD45RA+) naïve cells tended to decrease according to BMI and increased VAT. When all lymphocytic subpopulations were analysed according to the presence or absence of MS, no differences were found; nonetheless, when the MS and VAT variables were analysed together, it was observed that the total lymphocytes, memory cells (TCD3+CD45RO+) and TCD4+ increased and granulocytes decreased in patients with MS and increased VAT in relation to patients with MS and normal VAT, being these differences statistically significant. In performing diverse models of linear regression regarding patients with MS, monocytes and NK lymphocytes were negatively correlated to VAT, AM and SMM. When patients with MS were selected, also presenting increased VAT, only a statistically significant difference was found between monocytes and SMM. Two intervention groups were formed from the 169 research participants: one being subject to a physical activity (PhA) program (n=37) and the other to a diet plan (n=59). After intervention with PhA, participants were reported to work with 54 ±10.6% of their maximum level during the two months, where the lowest level was 46 ±13% over week 1 and the highest level was 61.9 ±10% over week 6. Regarding biochemical variables, it was observed a significant increase in triglycerides (TG); however, when each participant’s data were analysed separately, it was noticed that TG, glucose, LDL and total cholesterol decreased in approximately 62% of the participants in 27 ±12.6% and HDL-c increased in 52% of the participants in 20 ±10%, without these results being reflected when analysing these variables by groups. In relation to body composition and anthropometric measurements, it was found that only WC statistically decreased; TS, AM and SMM presented very limited changes. Also, it was observed that one person with obesity transitioned to OW, 2 persons transitioned from OW to normal weight and 2 persons with increased VAT transitioned to normality. Respecting lymphocytic subpopulations, it was found that total lymphocytes, TCD3+ and TCD8+ lymphocytes decreased, while granulocytes and naïve cells (TCD3+CD45RA+) increased significantly. No changes were found regarding helper and cytotoxic cells. Also, lymphocytic differential movement was observed according to BMI, where total lymphocytes, TCD3+ and TCD8+ decreased, while monocytes and TCD3+CD45RA+ lymphocytes increased significantly in participants with OW. In participants with obesity, total lymphocytes decreased and granulocytes increased significantly. Concerning statistically significant partial correlations of the (Δ) changes among leucocytic cells in relation to Δ in diverse variables, it was found that Δ at the peripheral level of granulocytes and TCD8+ lymphocytes were negatively correlated with Δ in WC; as well as TCD8+ lymphocytes positively correlated with Glu and LDLc. Δ of total naïve cells (TCD3+CD45RA+) positively correlated with Δ of Total Col. and LDL-c, while Δ of TCD4+CD45RA+ negatively correlated to Δ of TS and AM. On the other hand, 49% (n=29) of the participants of the weight-loss diet plan intervention reported normal BMI, 24% (n=14) reported OW and 27% (n=16) Ob. Only a prevalence of 13% (n=4) of MS was found. After the intervention, no significant changes were found in biochemical variables; however, once each participant’s data were analysed separately, TG, Glu, Total Col. and LDL-c decreased on average in 51% of the participants in 31.3 ±15% and the HDL-c increased in 56% in 6.9 ±4.4%. In relation to anthropometric and body composition measurements, it was found that WC, ST, AM and VAT decreased significantly. In regard to leucocytic cells after intervention, it was found that total lymphocytes and TCD4+ double positive cells (TCD4CD45RO+CD45RA+) decreased while TCD3+ lymphocytes increased. Once again, differential movement of lymphocytic subpopulations according to BMI was found, where total lymphocytes decreased and granulocytes increased in people with OW. Participants with obesity presented a decrease in TCD4+CD45RO+CD45RA+ lymphocytes and an increase in TCD3+ and TCD4+CD45RO+ lymphocytes, all these changes being statistically significant. In the matter of statistically significant partial correlations of Δ observed between leucocytic cells and diverse variables, it was found that Δ in monocytes correlated negatively with Δ in diastolic arterial tension (DAT) but correlated positively with Δ in ST, as well as Δ of NK lymphocytes did with TG. Also, a negative correlation was found between Δ of helper TCD4+ lymphocytes (TCD4+CD45RO+) and TCD4 memory lymphocytes (TCD4+CD45RO+) and the changes in WC and glucose, respectively. Finally, a positive correlation was reported between Δ in cytotoxic TCD8+ lymphocytes (TCD8+CD28-) and Δ in ST, and between Δ of TCD4+CD45RA+ and Total Col., LDL-c and WC. By way of general conclusion, the VAT and SMM increase in patients with OW and Ob. were important factors that influenced the presence of MS as well as caused immunologic changes at the peripheral level, the latter which could be compatible with the presence of a chronic inflammatory process. In addition, the implementation of modifications in HIIT and the weight-loss diet plan produced positive changes in the variables analysed; moreover, in relation to immune cells. All these findings suggest that both interventions had an impact on overweight and obese patients’ recovery from the inflammatory process, reflecting improvement in these participants’ health.; En la última década se ha mostrado claramente que en la obesidad existen alteraciones inmunofenotípicas a nivel de tejido adiposo y sistémicas, causadas por la excesiva e inapropiada activación del sistema inmune, por lo que a la obesidad se ha considerado como un proceso inflamatorio crónico de baja intensidad, el cual juegan un importante papel en la patogénesis y exacerbación de anormalidades metabólicas de la obesidad, particularmente de la resistencia a la insulina (RI) y dislipidemias generalizadas, como el síndrome metabólico (SM). Se ha propuesto que para rectificar tanto el problema de la obesidad como sus alteraciones inmunometabólicas, se implementen intervenciones basadas en modificaciones en el estilo de vida, principalmente incrementando la actividad física (AF) y la restricción de la ingesta calórica. El objetivo de la presente investigación fue establecer los cambios después de la implementación de una rutina de actividad física o de un plan de alimentación para reducción de peso, sobre células sistémicas del sistema inmune, y parámetros antropométricos, bioquímicos y de composición corporal, en adultos jóvenes con sobrepeso (SP) u obesidad (Ob), que presentaran o no SM. A los participantes se les realizó una historia clínica, se les midió estatura, peso y circunferencia de cintura (CC). Con el peso y la estatura, se pudo tener una primera clasificación del estado de nutrición de los participantes (normopeso, sobrepeso u obesidad). También se analizó la composición corporal con ayuda de los equipos Inbody720 y Hologic Wi; con el primero, se obtuvo el peso corporal y el TAV. El TAV permitió obtener el diagnóstico de obesidad visceral, donde presentar ≥100 cm2 de TAV diagnostica a una persona con obesidad visceral y ≤99 cm2 como con TAV normal. Con el equipo Hologic Wi, se obtuvieron los kilogramos de MME y porcentaje y kilogramos de tejido graso subcutáneo (TS y MG, respectivamente). De igual manera, se realizaron pruebas bioquímicas con la ayuda del equipo automatizado iKEM, con el cual se obtuvieron los niveles de triglicéridos (TG), colesterol de alta densidad (HDL-c), glucosa (Glu) y colesterol total (Col.Total). Para los niveles de colesterol de baja densidad (LDL-c) se utilizó la fórmula de Friedewald (Col. Total.- (HDL-c+TG/5). Para la toma de la presión arterial, se utilizaron los lineamientos de la Norma Oficial Mexicana (NOM-030-SSA2-1999), para la Prevención, Tratamiento y Control de la Hipertensión Arterial. Se realizó con un esfigmomanómetro por duplicado. El diagnóstico de SM se realizó de acuerdo con los criterios del Programa Nacional de Educación en Colesterol (ATP III: Panel de Tratamiento en Adultos III del Programa Nacional de Educación en Colesterol [por sus siglas en inglés: National Cholesterol Education Program Adult Treatment Panel III]) modificado para personas hispanas. Por último, se obtuvieron los porcentajes de las subpoblaciones linfocitarias (linfocitos totales, monocitos, granulocitos, linfocitos TCD3+, TCD4+, TCD8+, NK, B, células ayudadoras (CD4+CD62-), citotóxicas (CD8+CD28-), células de memoria (CD45RO+) y vírgenes (CD45RA+), tanto de TCD3+ como de TCD4+). Cuando se obtuvieron los datos mencionados previamente se inició el periodo de intervención durante dos meses. Éste consistió de una rutina de actividad física o de un plan de alimentación para reducción de peso. Al finalizar este periodo se realizaron de nuevo todas las mediciones. La etapa de entrenamiento estuvo basada de una adaptación del entrenamiento a intervalos de alta intensidad (HIIT, por sus siglas en inglés: High-Intensity Interval Training), mientras que el de plan de alimentación, se realizó con base en la dieta Enfoques Dietéticos para Detener la Hipertensión (DASH, por sus siglas en inglés: Dietary Approaches to Stop Hypertension). Entre septiembre de 2015 y enero de 2017 se incluyeron en la investigación un total de 169 personas con una edad media de 26.4±6.8 años, de los cuales 120 fueron mujeres (71%) y 49 hombres (29%); 34 presentaron un índice de masa corporal (IMC) normal (20%), 82 sobrepeso (49%) y 53 obesidad (31%). Se observó que conforme aumentó el IMC y estuvo presente el TAV incrementado, todas las variables antropométricas, de composición corporal y bioquímicas, se alteraron negativa y significativamente. La prevalencia de SM fue de 28% (n=45). Además, se encontró que las personas con SM tuvieron las cifras más altas significativamente en CC, TAV, kilogramos de MME y MG en relación con los sujetos sin SM. También, hubo correlación positiva entre TAV y MME, tanto en personas con SM como en ausencia de SM; siendo la correlación más fuerte entre personas que presentaron SM. Con respecto a las subpoblaciones leucocitarias, se encontró que los linfocitos totales aumentaron significativamente conforme lo hacia el IMC y estaba presente el SM y el TAV incrementado, en cambio los granulocitos y linfocitos NK por sus siglas en inglés: natural killer) disminuyeron significativamente conforme lo hacia el IMC y estaba presente el SM y el TAV incrementado. En el análisis de las células con funciones efectoras, no se encontraron diferencias estadísticas cuando se les analizó de acuerdo al IMC, SM o TAV. También se observó que las células de memoria totales (TCD3+CD45RO+) y las células TCD4+ incrementaron significativamente conforme al IMC y a la presencia de TAV incrementado. En cambio, las células vírgenes de TCD3+ (TCD3+CD45RA+) presentaron una tendencia a disminuir conforme al IMC y a la presencia de TAV incrementado. Cuando se analizaron todas las subpoblaciones linfocitarias de acuerdo con la presencia o no de SM, no se pudieron encontrar diferencias; sin embargo, cuando se unieron las variables de SM y TAV, se pudo observar que los linfocitos totales, células de memoria (TCD3+CD45RO+) y TCD4+ estuvieron incrementados y los granulocitos disminuidos en pacientes con SM y TAV incrementado en relación con pacientes con SM y TAV normal, siendo estas diferencias estadísticamente significativas. Al realizar distintos modelos de regresión lineal en personas con SM, se observó que los monocitos y los linfocitos NK correlacionaron negativamente con el TAV, la MG y la MME. Cuando se seleccionó a los pacientes con SM, que además presentaron TAV incrementado, sólo se encontró diferencia significativa entre monocitos y MME. De las 169 personas que se incluyeron en la presente investigación, se conformaron los dos grupos de intervención: el de actividad física (n=37) y de plan de alimentación (n=59). Después de la intervención con AF, se observó que los participantes estuvieron trabajando con un 54 ±10.6% de su nivel máximo durante los 2 meses, donde el nivel más bajo fue de 46 ±13% en la semana 1 y el más alto en la semana 6 (61.9 ±10%). En cuanto a las variables bioquímicas, se pudo observar aumento significativo de TG; sin embargo, cuando se analizó a cada uno de los participantes se pudo notar que los TG, la glucosa, el colesterol LDL y el total aproximadamente en el 62% de los participantes bajaron 27±12.6% y el HDL-c en el 52% de las personas aumentó 20±10% (datos no mostrados), sin verse reflejados estos datos en el análisis por grupo. En relación con las medidas antropométricas y de composición corporal, sólo la CC disminuyó estadísticamente; el TS, MG y MME mostraron cambios muy mesurados. Asimismo, se observó que una persona con obesidad pasó a SP, 2 con SP a peso normal y 2 personas con TAV incrementado pasaron a normalidad. En relación a las subpoblaciones linfocitarias, se encontró que los linfocitos totales, los linfocitos TCD3+ y TCD8+, disminuyeron, y granulocitos y células vírgenes (TCD3+CD45RA+) aumentaron significativamente. No se encontraron cambios en células ayudadoras y citotóxicas. Además, se presentó movimiento linfocitario diferencial de acuerdo al IMC, donde los linfocitos totales, TCD3+ y TCD8+ disminuyeron, y los monocitos y linfocitos TCD3+CD45RA+ aumentaron significativamente en personas con SP. En personas con obesidad, los linfocitos totales disminuyeron y granulocitos incrementaron significativamente. Con respecto a las correlaciones parciales estadísticamente significativas de los cambios (Δ) entre células leucocitarias en relación a los Δ en las distintas variables, se encontró que el Δ a nivel periférico de granulocitos y linfocitos TCD8+ correlacionó negativamente con los Δ en la CC; así como, los linfocitos TCD8+ positivamente con Glu y LDL-c. Los Δ de las células totales vírgenes (TCD3+CD45RA+) correlacionaron positivamente con los de Col. Total y LDL-c, y los Δ de las células TCD4+CD45RA+ correlacionaron negativamente con los Δ de TS y MG. Por otro lado, las personas que participaron en la intervención de plan de alimentación para reducción de peso, el 49% (n=29) presentaron un IMC normal, el 24% (n=14) SP y el 27% (n=16) Ob. Sólo se encontró una prevalencia de 13% (n=4) de SM. Después de la intervención no se pudieron encontrar cambios significativos en las variables bioquímicas; sin embargo, cuando se analizó a cada uno de los participantes se pudo notar que en promedio los TG, la Glu, el Col. Total y el LDLc en el 51% de los participantes, bajaron 31.3±15% y el HDL-c en el 56%, aumentó 6.9±4.4%. En relación con las medidas antropométricas y de composición corporal, se encontró que la CC, el TS, la MG y el TAV disminuyeron significativamente Con respecto a las células leucocitarias, después de la intervención se observó que los linfocitos totales y las células dobles positivas de TCD4+ (TCD4+CD45RO+CD45RA+) disminuyeron; mientras que los linfocitos TCD3+ aumentaron. También se encontró movimiento diferencial de las subpoblaciones linfocitarias de acuerdo al IMC, donde los linfocitos totales disminuyeron y los granulocitos aumentaron en personas con SP. En personas con obesidad, se presentó una diminución de los linfocitos TCD4+CD45RO+CD45RA+ y un incremento de linfocitos TCD3+ y TCD4+CD45RO+, siendo todos estos cambios estadísticamente significativos. En relación con las correlaciones parciales estadísticamente significativas de Δ observados entre las células leucocitarias y las distintas variables, se encontró que el Δ de monocitos correlacionó negativamente con los Δ en la tensión arterial diastólica (TAD), pero positivamente con los Δ en el TS, así como los Δ de los linfocitos NK con los TG. También se encontró correlación negativa de los Δ de linfocitos TCD4+ ayudadores (TCD4+CD62-) y linfocitos TCD4+ de memoria (TCD4+CD45RO+), con los cambios de CC y glucosa, respectivamente. Por último, se encontró correlación positiva de los Δ de linfocitos TCD8+ citotóxicos (TCD8+CD28-) con Δ de TS, y de los Δ de TCD4+CD45RA+ con Col.Total, LDL-c y CC. A manera de conclusión se puede que decir el aumento del TAV y la MME en pacientes con sobrepeso u obesidad, son factores importantes que influyeron en la presencia de SM; así como, causantes de cambios inmunológicos a nivel periférico que podrían tener compatibilidad con la presencia de un proceso inflamatorio crónico, y que la implementación de la modificación del HIIT como del plan de alimentación provocaron cambios positivos en las variables estudiadas, sobre todo en relación a la células inmunes. Todos estos hallazgos sugieren, que ambas intervenciones tienen un impacto sobre la recuperación del proceso inflamatorio presente en personas con sobrepeso y obesidad, reflejándose estos cambios en un mejor estado de salud de los participantes.